Primary biliary cholangitis: advances in understanding and management. (2nd March 2022) - Smith, Alex; Giles, Benjamin; Aspinall, Richard J
Abstract : Recent years have seen major advances in our understanding of primary biliary cholangitis, with the condition now renamed to reflect the majority of patients who do not have cirrhosis. Data from large multicentre studies have greatly increased our knowledge of the natural history of primary biliary cholangitis, making the identification of higher risk patients clearer and facilitating the development of new medications. Recent guidelines have emphasised the importance of risk stratification, targeted treatment of symptoms and early prioritisation for second line therapies. The review summarises recent major developments in our understanding of primary biliary cholangitis and its management.